Tropical natural fibre composites: properties, manufacture and applications - Salit, Mohd Sapuan (Springer-Verlag, 2014)
In this chapter, background of composite materials is presented followed by discussion of various major classification of composites such as polymer matrix composites, metal matrix composites and ceramic matrix composites, advanced composites, nanocomposites and natural fibre composites are made available to the readers. This chapter is presented as background information for the topic of the main concern in this book, i.e. tropical natural fibre reinforced composites. Tropical natural fibre composites are chosen because majority of the contents of this book are based on the work carried out on natural fibre composites in one of the tropical country, i.e. Malaysia.